Using social media to disseminate injury prevention content: Is a picture worth a thousand words? - Rebecca J. McAdams; Kristin J. Roberts; Elizabeth G. Klein; Jennifer A. Manganello; Lara B. McKenzie (New Prairie Press, 2021)
Social media (SM) offers an opportunity for injury professionals to disseminate reliable safety recommendations to parents, yet little is known about the reach and impact of SM messages on parental safety knowledge and safety behavior adoption. It is also unclear whether electronic health (eHealth) literacy level is associated with understanding of messages. Parents of children (< 7 years) were recruited from a nationally representative consumer panel to complete an online survey assessing their Internet and SM usage and eHealth literacy level using the eHealth Literacy Scale (eHEALS). Participants were shown three safety SM posts where images and text matched or did not match. A post-exposure survey captured participant understanding of SM post message. Five-hundred eighty parents completed the survey. A majority of participants were female (58.6%) with high eHealth literacy (84.5%). Compared to low eHealth literate parents, a larger proportion of high eHealth literate parents correctly identified the message in mismatched posts (safe sleep: p = .0081; poison prevention: p = .0052), while similar proportions of parents with high and low eHealth literacy correctly identified a matched post for bike safety (p = .7022). Within each eHealth literacy level, high eHealth literate parents were more often able to correctly identify SM post messaging when the photo and text matched. Parents are using SM to acquire safety, health, and parenting information; therefore, it is incumbent upon disseminators to create content with clear messages. SM posts should utilize matching text with imagery that illustrates the recommended safety behavior to facilitate parental understanding of safety recommendations, regardless of audience eHealth literacy level.